Intralesional corticosteroid injection as an effective treatment method for oral lesions: a meta-analysis (Brazilian Journal of Pharmaceutical Sciences, 2020)
Intralesional corticosteroid injection (ICSI) is known as one of the main methods used for treating a wide range of lesions. It also results in a high concentration of drugs at lesion sites, with minimal systemic absorption. Thus, this study aimed to provide a review of the intralesional corticosteroid injection (ICSI) indications in the treatment of oral lesions. To this end; relevant key words were searched in the databases of PubMed, Google Scholar, Scopus, ScienceDirect, and UpToDate in the present study. Accordingly, the results of a total number of 62 case reports or case series articles were used in this study and the positive therapeutic effects of intralesional corticosteroid injection (ICSI) in 23 common oral lesions were reported. The most common type of intralesional steroid in the treatment of oral lesions was triamcinolone. No significant difference was also observed in terms of pain in patients following the use of steroid alone or in combination with anesthetic agents; moreover, the reported side effects of this method were exceptionally rare and transient. It was concluded that the intralesional corticosteroid injection (ICSI) could be one of the effective therapeutic methods with no significant problems in many oral lesions such as inflammatory, immunologic, and vascular ones due to its higher therapeutic effects than other topical forms of steroids and fewer side effects than systemic corticosteroid.